Sandy Beach Macrofauna of Yucatán State (Mexico) and Oil Industry Development in the Gulf of Mexico: First Approach for Detecting Environmental Impacts - Guerra-Castro, Edlin; Hidalgo, Gema; Castillo-Cupul, Raúl E.; Muciño-Reyes, María; Noreña-Barroso, Elsa; Quiroz-Deaquino, Jaime; Mascaro, Maite; Simoes, Nuno (Frontiers in Marine Science, 2020)
The biodiversity of the coastal ecosystems in the Gulf of Mexico is threatened by anthropogenic activities of various kinds. The predominant portion of the land-sea margin in the State of Yucatán consists of exposed sandy beaches. This ecosystem is threatened by several activities that vary in spatial scales, at a local: cargo/fishing ports, touristic facilities, maritime traffic, and domestic pollution; and at a larger scale: the forthcoming development of the oil industry. In the absence of information about the biodiversity of these beaches, we implement the Marine Biodiversity Observation Network Pole to Pole sampling protocol to (1) Quantify the spatial patterns of diversity of macrofauna along the beaches; (2) quantify current levels of pollution by hydrocarbons (aromatic and aliphatic); (3) estimate sampling effort for future environmental impact assessments. During November 2018, six localities along the coastline of Yucatán State were sampled following a spatial hierarchical design that included three sites at each locality, and 9-18 core samples in the intertidal strata of each site. As a result, 31 species of invertebrates were registered. The patterns of distribution and abundance of species showed that there was a base community structure along the entire coast dominated by four species. In general, the density of species was relatively low (2-4 species/0.01 m3) and the density of individuals was high (20-200 ind./0.01 m3). The beta diversity was higher between localities with good environmental health, but the estimated alpha diversities did not show a pattern regarding the health of the coast. Lastly, the overall number of species reported suggest that gamma diversity of the macrofauna in the beaches of Yucatán is within the highest known worldwide. Levels of hydrocarbons detected in this study are exceptionally low compared to those reported for other coastal areas of the Gulf of Mexico and are several orders of magnitude lower than those considered as lower-threshold values for marine sediments. The biological and chemical patterns reported here indicated that it is an appropriate moment to start long-term monitoring. The sampling design we suggest is based on statistical precision and internationally recognized protocols for assessment of marine diversity on sandy beaches.